New Visions of the Child in Italian Cinema - Hipkins, Danielle 1973-; Pitt, Roger (Italian modernities, 2014)
The figure of the child has long been a mainstay of Italian cinema, conventionally interpreted as a witness of adult shortcomings, a vessel of innocence, hope and renewal, or an avatar of nostalgia for the (cinematic) past. New Visions of the Child in Italian Cinema challenges these settled categories of interpretation and reconsiders the Italian canon as it relates to the child. The book draws on a growing body of new work in the history and theory of children on film and is the first volume to bring together and to apply some of these new approaches to Italian cinema. Chapters in the book address aspects of industry and spectatorship and the varied film psychology of infancy, childhood and adolescence, as well as genres as diverse as silent cinema, contemporary teen movies, melodrama and film ethnography. The contributors engage with a wide range of modes and theories including neorealism, auteurism and contemporary postfeminism. The book maps out new roles for gender, the transnational, loss and mourning, and filmmaking itself, leading to a revised understanding of the child in Italian cinema